2006
DOI: 10.1002/eji.200535443
|View full text |Cite
|
Sign up to set email alerts
|

The Shiga toxin B‐subunit targets antigen in vivo to dendritic cells and elicits anti‐tumor immunity

Abstract: The non-toxic B-subunit of Shiga toxin (STxB) interacts with the glycolipid Gb 3 , which is preferentially expressed on dendritic cells (DC) and B cells. After administration of STxB chemically coupled to OVA (STxB-OVA) in mice, we showed that the immunodominant OVA 257-264 peptide restricted by K b molecules is specifically presented by CD11c + CD8a -DC, some of them displaying a mature phenotype. Using mice carrying a transgene encoding a diphtheria toxin receptor (DTR) under the control of the murine CD11c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 72 publications
2
70
1
5
Order By: Relevance
“…Cette corrélation est aujourd'hui discutée car elle pourrait dépendre plus de la durée du traitement que de la réponse clinique [34]. En revanche, les manifestations auto-immunes observées après administration de l'anticorps anti-CTLA-4 sont plus précoces et restent corrélées à la réponse au traitement [35,57] [39][40][41][42]. Ces nouveaux outils associés à l'identification de nouveaux adjuvants pour augmenter l'immunité cellulaire devraient permettre de mieux amplifier la réponse immune antitumorale sur les plans qualitatif et quantitatif.…”
Section: Trouver De Nouveaux Paramètres Cliniques D'évaluation De La unclassified
“…Cette corrélation est aujourd'hui discutée car elle pourrait dépendre plus de la durée du traitement que de la réponse clinique [34]. En revanche, les manifestations auto-immunes observées après administration de l'anticorps anti-CTLA-4 sont plus précoces et restent corrélées à la réponse au traitement [35,57] [39][40][41][42]. Ces nouveaux outils associés à l'identification de nouveaux adjuvants pour augmenter l'immunité cellulaire devraient permettre de mieux amplifier la réponse immune antitumorale sur les plans qualitatif et quantitatif.…”
Section: Trouver De Nouveaux Paramètres Cliniques D'évaluation De La unclassified
“…Un vaccin thérapeutique contre le cancer du col de l'utérus, fondé sur ce vecteur, est en cours de développement clinique par BT Pharma [28]. D'autres toxines bactériennes, comme la sous-unité B de la toxine de Shiga [29] ou l'antigène protecteur (PA) produit par Bacillus anthracis [30] sont également employés comme vecteurs d'antigènes. Des protéines de choc thermique, comme Hsp70 ou gp96, sont capables de se lier à divers récepteurs à la surface des CD, notamment au CD91 [31], et ont été employées dans plusieurs modèles expéri-mentaux pour vectoriser des antigènes [32].…”
Section: Stratégies De Ciblage Par Utilisation D'anticorps Spécifiqueunclassified
“…STxB has been used as a tool for the characterization of the retrograde route [13,14], and in biomedical research as a delivery tool for immunotherapy [3,15] and cancer targeting [16,17]. It was shown that STxB delivers exogenous peptides into the MHC class I and II pathways of human and mouse dendritic cells (DCs) and induces humoral and cell-mediated immune responses that protect mice from tumor growth [18][19][20][21][22]. Functional TAP and proteasome activities are required for STxB-induced MHC class I-restricted antigen presentation, strongly suggesting that STxB delivers exogenous antigenic proteins and peptides across membranes into the cytosolic compartment [19].…”
Section: Introductionmentioning
confidence: 99%